Rapid onset Akathisia with low dose AripiprazoleTwo Case Reports - Sreelakshmi Kameshwari, Jammalamdaka; Angothu, Hareesh; Devde, Raju (Indian Journal of Pharmacy Practice)
Akathisia is an extra pyramidal side effect with neuroleptic drugs which can be explained as a subjective desire to move or manifest restless movements like shuffling, tramping movements of legs/feet with objective evidence. Aripiprazole is a special category neuroleptic with a unique mechanism of action i.e., partial agonism to Doapmine D2 and Serotonin 5-HT1A receptor in addition to antagonistic activity at 5-HT2A receptor. Long term and short term clinical trials have validated minimal extra pyramidal symptoms with Aripiprazole when compared to other conventional and atypical neuroleptics. Here we project two cases of rapid onset akathisia developed in a 17 year old male patient and 45 year old male patient who received Aripiprazole as an adjuvant in obsessive compulsive disorder. In both the cases there was a rapid onset of akathisia symptoms, in the first case within 15 days and in the second one he developed next day which turned more severe within 10 days. A global score of 4 was obtained on Global Barnes Akathisia Rating Scale in both cases. In both the cases after dechallenge (dose reduction in first case and withdrawal in second case) of the offending agent there was alleviation of symptoms without any further intervention and the patients have shown signs of recovery within a week.
Keywords: Aripiprazole; Akathisia; A typical antipsychotics; Extra pyramidal side effects; Dechallenge; Barnes Akathisia Rating Scale